(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper analyzes how indigenous frameworks form a basis for women's response to disasters by examining the structural (historical Ima Keithel network: Mothers' Market), social (Meira Paibi: Women Torchbearers) and operational dimensions of leadership in disaster management within grassroots institutional structures embedded into socio-cultural history. A mixed-methods design using an explanatory sequential approach was employed; quantitative data were collected through structured questionnaires administered to 384 leaders from five districts (Imphal West, Imphal East, Thoubal, Churachandpur and Ukhrul) while qualitative key informant interviews of twelve respondents. The results of SEM indicated that structural social capital ( = .342, p < .001) and cognitive social capital ( = .418, p < .001) positively predict community disaster resilience, grassroots institutional trust ( = .215, p < .01) mediates between informal women networks and operational evacuation efficiency, and there is a significant mismatch between informal disaster response capacity and formal institutional integration (87.5% respondents report zero formal representation within State and District Disaster Management Authorities (SDMA/DDMA)). Qualitative thematic analysis showed that women networks have rapid resource mobilization and localized risk communication, but they are systematically constrained by patriarchal institutional structures, lack of financial autonomy, and non-recognition in formal policy frameworks. This study offers an empirical model for integrating grassroots, gender-led social capital into state-level DRR policies for community resilience building in complex emergency settings.